Longitudinal Force Bearing Capacity Analysis of Slave Locomotiveswith 13A/QKX100 Coupler/Draft Gear System in Heavy Haul Train - YANG Xiang-jian; WU Qing; HE Yong-qiang; ZHANG Tao (机车电传动)
For studying longitudinal force bearing capacity of slave locomotives in heavy haul trains, nonlinear draft gear models and detailed coupler models were developed after the analysis of working mechanism of 13A/QKX100 coupler/draft gear systems. By utilizing a train model consisted of one HXD1 8-axle locomotive and two C80 freight wagons, dynamic behavior of coupler systems bearing longitudinal forces were analyzed and longitudinal force bearing capacity of slave locomotives was obtained. Study results showed that wheelset lateral force increased with longitudinal compressive force and coupler free angles, but not so obvious while coupler angles were small. Longitudinal compressive force bearing capacity of slave locomotives were larger than 2 500 kN when coupler angles smaller than 6 degrees or the coupler systems had frictional stability structure.